Efeitos do programa Mais Médicos no desempenho das equipes de saúde da família do estado da Paraíba no 3o ciclo do PMAQ-AB - Pereira Neto, Pedro Celestino (2022)
The Mais Médicos Program involved restructuring strategies for health units, changes in the curriculum of medical schools, expansion of undergraduate and residency vacancies, in addition to the emergency supply of doctors. The Primary Care Access and Quality Improvement Program was one of the largest primary care assessment programs in Brazil, assessing the quality of services and seeking to expand access and improve this quality. Since the Mais Médicos Program was related to an improvement in the quality of care in Primary Care by different studies, it would be reasonable to think that this would have an effect on the evaluation of the Program for Improving Access and Quality in Primary Care. In the same sense, the objective of this work is to evaluate the effects of the Mais Médicos Program on the certification scores and indicators of the Program for Improving Access and Quality of Primary Care of teams in the state of Paraíba. It is a study with a quantitative approach, mixed ecological type, retrospective, longitudinal, evaluating the relationship between the two programs. Initially, studies that could demonstrate some effect of the Mais Médicos Program on the indicators evaluated by the Program for Improving Access and Quality of Primary Care were evaluated. A survey was carried out in the Scielo, Pubmed and BVS / Bireme databases, looking for articles whose results were somehow related to the dimensions and subdimensions evaluated in this program. The evolution of grades between the 1st and 3rd cycles of this program was evaluated through a paired t-test and a t-test for independent samples was also performed in order to compare the difference in grade averages between the group that had at least 30 months of the Mais Médicos Program and the group that had the program for a period of less than 30 months. The relationship between the length of time as a doctor in the Mais Médicos Program and the certification scores of the family health teams was also evaluated, as well as the relationship between this program and 34 health indicators of the Program for Improving Access and Quality of Primary Care. A simple linear regression was also performed in order to assess the influence of the Mais Médicos time on the grade of the 3rd cycle of the Program for Improving Access and Quality of Primary Care. After verifying the contribution of Mais Médicos to improving the grade of the 3rd cycle, its contribution to each of the 34 predictors that represented the independent variables was investigated, choosing to use the technique of discriminant analysis, in order to identify which independent variables discriminate better between the 2 groups. The results of this study were presented from 3 articles, the 1st article being an integrative review about the relationship between the Mais Médicos Program and the dimensions evaluated by the Program for Improving Access and Quality of Primary Care, which identified, from the studies on Mais Médicos, which showed effects on several indicators: infrastructure; work management, continuing education; home visit; monitoring of users with chronic conditions, women's health; monitoring of traditional communities; access and appointment scheduling, bonding and accountability; satisfaction with care; and user participation. The 2nd article comparing the grades of the 1st and 3rd cycles, between teams that had and did not have the Mais Médicos, identified a statistically significant difference in the average of the grades of the 3rd cycle between group 0 and group 1. Finally, a 3rd article evaluating the effects of the Mais Médicos Program on the performance of the teams, demonstrating the positive impacts of the program on the grades and indicators of the 3rd cycle in Paraíba. Thus, it was possible to conclude that the Mais Médicos Program had positive effects on the performance of health teams in the Program for Improving Access and Quality of Primary Care, showing the confluence of the two programs for the qualification of Primary Care actions.